Fatty Acids Composition of Some Pomegranate (Punica granatum L.) Varieties Grown in Southeastern Anatolia Region in Turkey - ERCISLI, SEZAI; ORHAN, EMINE; HIZARCI, YASEMIN (Asian Journal of Chemistry, 2010)
In this study, fatty acids composition in the aril (edible part) of 6 pomegranate (Punica granatum L.) varieties grown in Southeastern Anatolia region of Turkey were determined by using gas chromatography. The pre-dominant fatty acid in pomegranate arils was found linolenic acid (54.58-61.06 %) and followed by palmitic acid (19.36-30.67 %), linoleic acid (0.00-11.35 %), oleic acid (2.37-6.17 %), stearic acid (0.61- 4.12 %) and myristic acid (0.28-0.94 %). The differences among pomegranate varieties in terms of fatty acid compositions suggested that fatty acid profile could be useful for chemotaxonomic classification.